THE EFFECT OF REALITY APPROACH GROUP COUNSELING SERVICES ON TOXIC FRIENDSHIP COMMUNICATION AT AL-WASHLIYAH MUSLIM UNIVERSITY MEDAN - Wildani Auza Suroya; Ika Sandra Dewi (Literasi Nusantara, 2022)
This research was carried out based on the phenomena that exist among students, the problems that occur in students are toxic friendship communication, so to see how high the behavior is, the researchers conducted research at the Muslim Nusantara University Al-Washliyah. Problems that can be seen from the friendships made by students both in terms of speech and actions. Such as not wanting to lose to friends, not respecting opinions, depending on others, stubbornness and lack of empathy for fellow students. This research was shown after the treatment was given to 8 students. Counseling services as a form of treatment that researchers provide to see if there is a decrease in toxic friendship communication behavior in students. The real effect is obtained from the results of the linear regression test that the researchers did to find out whether there is an influence by providing group counseling services with a reality approach to toxic friendship communication. to predict the communication variable toxic friendship.